Simulation model of the characteristics of syngas from hardwood biomass for thermally integrated gasification using unisim design tool. (15th November 2020) - Usmani, Sameer; Gonzalez Quiroga, Arturo; Vasquez Padilla, Ricardo; Palmer, Graeme; Lake, Maree
Abstract: Gasification is a potential clean technology for producing thermal and electric power from biomass. Major issues with gasification are the presence of heavy compounds known as tar in the syngas and the provision of thermal energy to the process. These issues discourage the low-scale implementation of gasification technology because of high capital and operating costs. This paper proposes a simulation model that harnesses a thermal integration between low-temperature and high-temperature gasification stages. The proposed configuration can potentially generate condensable low-temperature gasification vapors as well as syngas with relatively low tar content. The UniSim model uses hardwood biomass and steam as the gasifying agent. Results show that CO decreases while H2 increases with an increase in the steam/biomass-ratio within the temperature range 600–1200 °C. The minimum mole fraction of CO approached 3.1% at 600 °C, while H2 exhibited a maximum with 35.2% at that temperature. The maximum mole fraction of CO was 13.2%, while H2 approached 31.2% at 1200 °C. The heating value of syngas decreased with an increase in steam/biomass ratio but increased with a rise in temperature. This work provides a first indication of the thermodynamic feasibility of the concept; the next step is validation in a dedicated setup. Highlights: Two-stage gasification concept model for thermal integration modeled on UniSim. Hardwood used as feed and steam as a gasifying agent in the numerical concept model. Rising steam/biomass lead to high heat values while rising T has opposite effect. This is a conceptual model to demonstrate thermal integration between the stages.